Beyond the organisation and beyond the nation state...and the employment relationship, same as it ever was? Global value chains and the challenges for Industrial Relations Research - Helen Rainbird; Pamela K. Robinson (University of Birmingham, Birmingham Business School, 2013)
Global value chain (GVC) analysis (e.g. Gereffi, 1994) has been developed to understand the potential for developing countries and companies to upgrade production processes and capture value. Theoretically pluralist, it provides a methodological framework for posing research questions about the nature of globalisation. For Industrial Relations scholars it raises questions about the role of lead companies in setting standards amongst suppliers in the value chain, the influence of private labour codes and standards, Corporate Social Responsibility policies, forms of supranational regulation, and the role of civic society organisations in pressing for labour standards. New research questions are raised which require looking beyond the traditional components of the Industrial Relations system - the state, employers and unions - requiring inter-disciplinary engagement with debates in Development Studies and Economic Geography, and with researchers from the 'global South'.
Keywords: 330; Global value chain analysis; labour regulation; public and private standards; Industrial Relations research